2002
DOI: 10.1128/jb.184.11.2925-2930.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the HspR-Mediated Stress Response inHelicobacter pylori

Abstract: The major heat shock genes of Helicobacter pylori are regulated by the HspR repressor. In the present study we characterize the transcriptional response of the three known HspR-dependent promoters P cbp , P gro , and P hrc to different environmental stresses. A temperature shift from 37 to 42°C causes a typical heat shock response at all three promoters characterized by an immediate and strong induction phase of transcription and a subsequent adaptation phase, which is specific for each promoter and whose onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…The transcript quantification in Fig. 5B shows that the maximal induced level is ϳ5-fold higher than in nonstressed cells, thus confirming previous results obtained in our laboratory (36). In contrast, in G27(P gro ::cat) cells virtually no increase in transcription can be observed at the P gro promoter after temperature upshift, indicating that transcriptional control is lost in this mutant.…”
Section: Vol 186 2004 Regulation Of Heat Shock Genes In H Pylori 2961supporting
confidence: 89%
See 2 more Smart Citations
“…The transcript quantification in Fig. 5B shows that the maximal induced level is ϳ5-fold higher than in nonstressed cells, thus confirming previous results obtained in our laboratory (36). In contrast, in G27(P gro ::cat) cells virtually no increase in transcription can be observed at the P gro promoter after temperature upshift, indicating that transcriptional control is lost in this mutant.…”
Section: Vol 186 2004 Regulation Of Heat Shock Genes In H Pylori 2961supporting
confidence: 89%
“…Total H. pylori RNA was isolated as described previously (36). Transcription from the P gro and P hrc promoters was assayed by primer extension analysis with oligonucleotides groS and hrcA as detailed previously (35,36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA preparations were performed essentially as described by Spohn et al (40). S. flexneri strains M90T (wild type) and SF622 (ipaD) were grown in 25 ml of LB broth at 37°C to mid-log phase and harvested.…”
Section: Methodsmentioning
confidence: 99%
“…Initial studies indicated that while transcription of the groESL and cbpA-hspR-orf operons was strongly inducible by treatment with 300 mM NaCl, no induction was observed when cultures were incubated at 45°C (31). Subsequently, Homouth and coworkers (15) showed that transcription of these operons is strongly inducible by a mild heat shock at 42°C, suggesting that HspR can indeed mediate the transcriptional response to a sudden temperature increase, characterized by fast and strong induction of transcription and a subsequent shutoff phase, whose onset is determined largely by the stability of the respective mRNAs (29). Until recently, the study of HrcAdependent regulation was hampered by difficulties in purifying a recombinant protein to map the HrcA binding sites on the promoters (25,31).…”
mentioning
confidence: 99%